Weak and Strong Sustainability of Irrigation: A Framework for Irrigation Practices Under Limited Water Availability - Borsato, Eros; Rosa, Lorenzo; Marinello, Francesco; Tarolli, Paolo; D'Odorico, Paolo (Frontiers in Sustainable Food Systems, 2020)
Agriculture strongly relies on irrigation. While irrigated land accounts for roughly 20% of the global cultivated area, it contributes to about 40% of crop production. In the last few decades, the growing demand for agricultural commodities has translated into an increasing pressure on the global freshwater resources, often leading to their unsustainable use. Here we investigate the sustainability of irrigation, balancing farmers’ profit generation objectives and the needs of ecological systems. We ask the question “sustainability of what?”, to stress how the sustainability of irrigation is often evaluated with respect the opposing needs of humans and nature. While from the farmers’ perspective irrigation is sustainable when it provides uninterrupted access to water resources at a price not exceeding the marginal revenue they generate (clearly without accounting for environmental externalities), from the standpoint of water resources, irrigation is sustainable if it does not deplete freshwater stocks or environmental flows. We invoke the notions of ‘weak’ and ‘strong’ sustainability to develop a novel framework for the evaluation of tradeoffs between human needs and the conservation of natural capital. Through the analysis of criteria of performance, we relate water deficit and irrigation overuse to the reliability and resilience of irrigation. This approach is applied to the case of Australia, a major agricultural country affected by water scarcity. The application of the framework to the case of Australia shows how this approach can be used to highlight areas in which irrigation contributes to a weakly sustainable use of water resources with impacts on environmental flows and groundwater stocks. Solutions, such as increasing efficiencies or reducing water applications through the adoption of deficit irrigation, can enhance water sustainability in some water scarce locations.